Weekday and weekend variation in the distribution of daily stepping in 9-11 years old obese school children - Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Hasmiza, Halib; N.N., Aziz; M., Rahim (2017)
A major health threat for children in the 21st century is physical inactivity in conjunction with the elevated prevalence of obesity.In Malaysia, low physical activity among children is a major concern. The objective of the study was to analyze the day to day variation of step count in a sample of obese children using the activPALTM monitor. This was a cross sectional study conducted in Kuala Terengganu, Terengganu. The sample compromised 41 boys and 24 girls between the ages of 9-11 years. Number of steps was objectively measured using an activPALTM accelerometer over a period of 4-7 days and had their height and weight measured. Mean step count from this sample of obese children was 8861 ± 3157steps. Steps per day were significantly higher for boys compared to girls (p=0.034). Obese children took significantly more steps at weekdays than on weekends (p=0.001). Steps/hour were significantly higher in weekday compared to weekend between 0600 to 0700 (p<0.001), 0700 to 0800 (p<0.001), 0800 to 0900 am (p<0.001), 0900 to 1000 (p=0.032), 1000 to 1100 (p=0.046), 1100 to 1200 (p<0.001), 1300 to 1400 (p=0.002), 1400 to 1500 (p<0.001), 1800 to 1900 (p=0.026) and 2000 to 2100 (p=0.019). Detailed daily patterns of physical activity are required to fully understand the differences across days that help future interventions to target those falling short particularly during weekend.